DAMPAK PROGRAM AMNESTI PAJAK TERHADAPKEMAUANWAJIB PAJAK(WP) DALAM MEMBAYARPAJAKSESUAI DENGANUUNO. 11TAHUN2016 - Edy Susanto; Marhamah Marhamah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
Taxation is still an interesting topic to discuss. A number of tax cases that have emerged lately have made people reluctant to pay taxes. This certainly has a negative impact on the government's efforts to increase state revenues through taxes. Law No. 11 was issued in 2016 concerning Tax Amnesty where taxpayers can report assets and debts that have not been reported at the Last Annual SPT and only pay ransoms in accordance with the law. The population in this study is the Individual Taxpayer who participates in the tax amnesty program in the work area of ​​the Semarang City Tax Service Office who participates in the 9,484 tax amnesty program, while the sample taken using the Slovin formula is obtained by 100 respondents. The method of analysis uses multiple linear regression. The results showed that the Random Audit Strategy had a significant effect on Taxpayer Compliance at the Primary Tax Office in the City of Semarang. Perceived probability of audit variable has a significant effect on Taxpayer Compliance at the Primary Tax Service Office in Semarang City, the Taxpayer Attitude variable has a significant effect on Taxpayer Compliance in the Primary Tax Service Office in Semarang City, and Taxpayer Compliance variable has a significant effect on Office Revenue Increase Primary Tax Service in Semarang City. The number of coefficient of determination in the first model shows the number of coefficient of determination (Adjusted R Square) of 0.467. While the number of coefficient of determination of the second model shows the number of coefficient of determination (Adjusted R Square) of 0.60.